Joint Neighbor Discovery and Topology Exchange With Directional Antennas in Multi-Hop MANETs - Yu Liu; Long Chen; Huiyuan Xu; Dalong Yang; Tao Cao; Youjiang Liu (IEEE Access)
As a crucial step for routing establishment in multi-hop mobile ad hoc networks (MANETs), topology discovery (TD) is extremely challenging when directional antennas are used. In this paper, we propose a joint neighbor discovery and topology exchange (JNDTE) algorithm for the purpose of fast TD. By arranging one topology-information exchange (TIE) closely following the occurrence of one successful neighbor discovery for any pair of nodes, the TD time is significantly decreased due to the avoidance of beam misalignment during the TIE process. Besides, a beam selection strategy is utilized to dynamically adjust the probability distribution for each beam sector to further speed up the TD process. Simulation results show the superiority of the proposed algorithm.